2018
DOI: 10.1590/1679-78254710
|View full text |Cite
|
Sign up to set email alerts
|

Experimental analysis of the efficiency of steel fibers on shear strength of beams

Abstract: The efficiency of steel fibers for shear strength of reinforced concrete beams is assessed. Four beams were evaluated: control consisted of one beam without any steel fibers and three beams with reinforced concrete with steel fibers. All beams were reinforced for shear strength by a minimum reinforcement rate. The influence of fiber content added to concrete, at 0.5%, 0.8% and 1.0%, and the possibility of partial or total replacement of conventional shear reinforcement (stirrups) by steel fibers were evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…It was evident that the reinforcement ratio over 1% allowed an increase up to 20% in the shear strength in SFRC, as observed in beams VF-1 and VF-2. [20], which represents an estimate for the failure modes of the beams, which can be by shear with indicated that all beams presented shear failure, as observed in the tests. Figures 12a and 12b clearly show the behavior of the flexural reinforcement influence in the failure mode, a similar linear behavior for both the RC beams and the SFRC beams.…”
Section: Effect Of Longitudinal Reinforcementmentioning
confidence: 84%
“…It was evident that the reinforcement ratio over 1% allowed an increase up to 20% in the shear strength in SFRC, as observed in beams VF-1 and VF-2. [20], which represents an estimate for the failure modes of the beams, which can be by shear with indicated that all beams presented shear failure, as observed in the tests. Figures 12a and 12b clearly show the behavior of the flexural reinforcement influence in the failure mode, a similar linear behavior for both the RC beams and the SFRC beams.…”
Section: Effect Of Longitudinal Reinforcementmentioning
confidence: 84%
“…Notably, the ultimate shear strength exhibited the most substantial improvement of 164% in two beams: the first beam was reinforced with 1.5% steel fibres and stirrups (diameter 6 mm, spacing 200 mm), while the second beam was reinforced with 1.0% steel fibres and stirrups (diameter 6 mm, spacing 100 mm) [12]. Another study [13] investigated four beams, comprising a control beam without steel fibres and three beams with steel fibres added at ratios of 0.5%, 0.8%, and 1%. The researchers concluded that the inclusion of steel fibres improved the shear capacity of the tested beams, transforming the failure mode from brittle to flexural.…”
Section: Introductionmentioning
confidence: 99%
“…Tahenni et al (2016) presented effect of steel fibers on the shear behavior of high strength concrete beams. Gomes et al (2018) presented experimental analysis of the efficiency of steel fibers on shear strength of beams. Hamoodi et al (2021) presented a shear behavior of fiber-reinforced concrete beams: an experimental study.…”
Section: Introductionmentioning
confidence: 99%